2013
DOI: 10.4103/2278-0513.121521
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of correlation between p53 codon 72 polymorphism and risk of bladder cancer in Moroccan patients

Abstract: Background:The p53 codon 72 polymorphism has been investigated extensively for its association with various cancers around the world. Several studies have investigated the association between p53 polymorphism at codon 72 and risk of developing bladder cancer, but the results are still controversial. Aim: The aim of our study was to evaluate the association between the p53 polymorphism and the bladder cancer risk among Moroccan patients. Materials and Methods: This study was carried out on fresh biopsies from 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Yet, no association was observed with TP53 c.215G>C, p. (Arg72Pro) SNP and the risk of bladder [41] and cervical carcinomas [42] in Moroccan population. Numerous studies have reported a significant association between TP53 c.215G>C, p. (Arg72Pro) polymorphism and the development of other malignancies [43][44][45][46].…”
Section: Discussionmentioning
confidence: 86%
“…Yet, no association was observed with TP53 c.215G>C, p. (Arg72Pro) SNP and the risk of bladder [41] and cervical carcinomas [42] in Moroccan population. Numerous studies have reported a significant association between TP53 c.215G>C, p. (Arg72Pro) polymorphism and the development of other malignancies [43][44][45][46].…”
Section: Discussionmentioning
confidence: 86%